Prevalencias de la diabetes y su relación con las complicaciones en los pacientes diabéticos que acuden al Sub Centro de Salud del cantón La Maná durante el año 2015 - Herrera Sandoval, Alicia Maribel (2016)
This research on the findings of the study that was conducted in the Canton La Maná Province of Cotopaxi, in order to determine the prevalence of diabetes and its relation to complications in diabetic patients attending the sub health center presents Canton La Maná during 2015. It was found in those who exercise to prevent complications of his illness 31.43% if you know that the use of alcohol, snuff and caffeine, 8.57% unaware that the use of snuff, alcohol and caffeine impairs their health while those they say a healthy nutrition 11.43% if you know that the use of alcohol, snuff and caffeine harms but unknown 22.86% and those who say the self carry a 14.29% if they know these rules but not know them say 11.43%the consequences will be established in those who suffer from diabetes and that if they know the origin of his illness 11.43% suffer from diabetic foot and within the same parameter an 8.57% of neuropathy one 11.43% of retinopathy, 14.29% of nephropathy 17 -14% of coronary heart disease and hypertension 22-86% while those who know the origin of his illness 1.14% had diabetic foot neuropathy 2.86% 1.71% 2.86% retinopathy, nephropathy 3.43% of coronary heart disease and 2.29% of hypertension. It was evident that those who have family support removed the 48.57% medicine every 30 days in sub health centers, 40% say they do not feel this family support in everyday life while those who retire each medication 45 days 2.86% if the consent of family support and 8.57% are unaware of the help that gives your family is of vital importance that families give full support to those with catastrophic illnesses. Keywords: Diabetes, prevalence, insulin, retinopathy, hypertension, nephropathy, heart disease, nutrition, endocrine disorders, glucose.